ijps 2021
DOI: 10.36468/pharmaceutical-sciences.spl.267
|View full text |Cite
|
Sign up to set email alerts
|

Bardet-Biedl Syndrome 4 in Early Diagnosis and Prognosis of Breast Cancer

Abstract: Zhang et al.: Bardet-Biedl Syndrome 4 in Breast CancerBardet-Biedl syndrome 4 is the key protein to control cilia formation. In this study, bioinformatics method was used to screen the core genes related to the prognosis of breast cancer by analyzing the gene chip data of gene expression omnibus and the cancer genome atlas database, so as to provide a new candidate target for the treatment of breast cancer. Data were downloaded from the cancer genome atlas, gene expression omnibus to evaluate Bardet-Biedl synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The overexpression of PRC1 also indicates a poor prognosis [39]. Moreover, BBS4 has been observed down-regulated in breast cancer and indicates a shorter survival time [40]. Collectively, these findings suggest that circHUNK play potential roles in the downstream disturbance of cell division in SOV via competing endogenous RNA mechanisms (Fig.…”
Section: Circrna's Competing Endogenous Gene Pairsmentioning
confidence: 83%
See 1 more Smart Citation
“…The overexpression of PRC1 also indicates a poor prognosis [39]. Moreover, BBS4 has been observed down-regulated in breast cancer and indicates a shorter survival time [40]. Collectively, these findings suggest that circHUNK play potential roles in the downstream disturbance of cell division in SOV via competing endogenous RNA mechanisms (Fig.…”
Section: Circrna's Competing Endogenous Gene Pairsmentioning
confidence: 83%
“…Wang et al found that lncHCP5/miR-525-5p/PRC1 crosstalk might promote malignant behaviors of ovarian cancer cells and the silencing of lncRNA HCP5 impeded growth and metastasis of tumour in mice [38]. BBS4 was differentially expressed and downregulated in breast cancer and it was associated with poor prognosis [40]. Collectively, these findings inferred that the circHUNK in this cceGP might be associated with the regulation of gynecologic cancer and might be a potential target for anticancer drugs.…”
Section: Discussionmentioning
confidence: 95%
“…The overexpression of PRC1 also indicates a poor prognosis[42]. Moreover, BBS4 has been observed down-regulated in breast cancer and indicates a shorter survival time [43]. Collectively, these findings suggest that circHUNK play potential roles in the downstream disturbance of cell division in SOV via competing endogenous RNA mechanisms ( Figure 6I ).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al found that lncHCP5/miR-525–5p/ PRC1 crosstalk might promote malignant behaviors of ovarian cancer cells and the silencing of lncRNA HCP5 impeded growth and metastasis of tumour in mice [41]. BBS4 was differentially expressed and downregulated in breast cancer and it was associated with poor prognosis [43]. Collectively, these findings inferred that the circHUNK in this cceGP might be associated with the regulation of gynecologic cancer and might be a potential target for anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the expression profiles of the ESR1 signature (spot S, Pearson correlation coefficient: 0.24-0.82, top correlated genes: SCUBE2, ESR1, ABCC8, RALGPS2, APH1B, BBS4, MYB, GALNT10, LMX1B, HHAT, [86][87][88][89][90] Supplementary Table S24 in Supplementary_Tables_S17-S24.xlsx file of "Extended data", see Data and software availability) were significantly downregulated in Lum B, HER2E, basal, and normal-like cancers, while were significantly upregulated in the Lum A subtype. In addition, the methylation profiles in the basal subtype were significantly increased compared to the true normal tissue.…”
Section: Estrogen Receptor Signaling (Spot S)mentioning
confidence: 99%